PENGARUH TINGKAT INFLASI, DEBT TO EQUITY RATIO DAN RETURN ON EQUITY TERHADAP HARGA SAHAM - Chusnul Astriana; Eko Widodo; Guntur Kusuma Wardana; Dian Ratih (Commodities, Journal of Economic and Business, 2023)
This thesis aims to determine the effect of inflation rate, debt to equity ratio, return on equity to stock prices of property services sector property and real estate. The study was conducted at IDIS Investment Gallery of UNISKA by using secondary data. The population in this study as many as 48 companies then set sample in this study as many as 7 companies Property and Real Estate listed on the BEI period 2014-2016 which has been selected using purposive sampling method by using several criteria in taking samples. The data analysis technique used in this research is classical assumption test consisting of normality test, multicolinearity test, heteroscedasticity test and autocorrelation test, then test multiple linier regression analysis and use hypothesis test consisting of coefficient of determination test, t-test test ( partially), F-test (collectively). The result of research stated that with regression equation that Y = 7,821,482-1,735,657X1 + 1,176,411X2 + 532,696X3 can be concluded partially inflation rate have negative and significant effect to stock price with t value equal to -2,429 and significance value <0, 05 equal to 0,027, debt to equity ratio partially positive and not significant to stock price with t value equal to 0,3999 and significance value> 0,05 equal to 0,695 and return on equity partially have positive and significant effect to share price with value t count of 4.257 and significance value <0.05 of 0.001. Together the rate of inflation, debt to equity ratio and return on equity effect on stock prices with F arithmetic of 8.160 and significance value <0.05 of 0.001.